High-Intensity Interval Training with Vibration as Rest Intervals Attenuates Fiber Atrophy and Prevents Decreases in Anaerobic Performance - Mueller, Sandro Manuel; Aguayo, David; Zuercher, Matthias; Fleischmann, Oliver; Boutellier, Urs; Auer, Maria; Jung, Hans H.; Toigo, Marco (PloS one, 2015)
Aerobic high-intensity interval training (HIT) improves cardiovascular capacity but may reduce the finite work capacity above critical power (W') and lead to atrophy of myosin heavy chain (MyHC)-2 fibers. Since whole-body vibration may enhance indices of anaerobic performance, we examined whether side-alternating whole-body vibration as a replacement for the active rest intervals during a 4 x 4 min HIT prevents decreases in anaerobic performance and capacity without compromising gains in aerobic function. Thirty-three young recreationally active men were randomly assigned to conduct either conventional 4 x 4 min HIT, HIT with 3 min of WBV at 18 Hz (HIT+VIB18) or 30 Hz (HIT+VIB30) in lieu of conventional rest intervals, or WBV at 30 Hz (VIB30). Pre and post training, critical power (CP), W', cellular muscle characteristics, as well as cardiovascular and neuromuscular variables were determined. W' (-14.3%, P = 0.013), maximal voluntary torque (-8.6%, P = 0.001), rate of force development (-10.5%, P = 0.018), maximal jumping power (-6.3%, P = 0.007) and cross-sectional areas of MyHC-2A fibers (-6.4%, P = 0.044) were reduced only after conventional HIT. CP, V̇O2peak, peak cardiac output, and overall capillary-to-fiber ratio were increased after HIT, HIT+VIB18, and HIT+VIB30 without differences between groups. HIT-specific reductions in anaerobic performance and capacity were prevented by replacing active rest intervals with side-alternating whole-body vibration, notably without compromising aerobic adaptations. Therefore, competitive cyclists (and potentially other endurance-oriented athletes) may benefit from replacing the active rest intervals during aerobic HIT with side-alternating whole-body vibration. ClinicalTrials.gov Identifier: NCT01875146.